Cover Feature: The Intermediates in Lewis Acid Catalysis with Lanthanide Triflates (Eur. J. Org. Chem. 22/2019). Issue 22 (29th May 2019) - Tripodi, Guilherme L.; Correra, Thiago C.; Angolini, Célio F. F.; Ferreira, Bruno R. V.; Maître, Philippe; Eberlin, Marcos N.; Roithová, Jana
Abstract : The Cover Feature shows spectro‐scopic probing of intermediates in lanthanide catalyzed Knoevenagel condensation. The lanthanide reaction complexes were fished out from the reaction mixture by electrospray ionization mass spectrometry. The IR spectroscopic features of the lanthanide reaction complexes directly correlate with the observed reactivity in solution. Artwork by Koen Segers and acknowledgments to C. F. F. Angolini. More information can be found in the Full Paper by M. N. Eberlin, J. Roithová et al.